Pengaruh Endorser Arief Muhammad Terhadap Minat Beli Konsumen Pada Produk Cakekinian - Prismadini, Maylia Ajeng (Universitas Mercu Buana, 2022)
The strategy carried out by the company in increasing the sales value of products through advertising elements, one of which is determined by the Endorser. This study aims to determine the influence of endorser Arief Muhammad on consumers' buying interest in contemporary cake products. In the concept of celebrity endorser according to Terence A. Shimp, there are 5 dimensions known as TEARS. And the concept of buying interest used in this study is the AIDA model theory initiated by Kotler & Keller. The research method in this study uses a quantitative approach with a survey method. The data collection technique uses a non-probability sampling technique. The respondents are active followers of the instagram account @cakekinian.official. The results showed that the credibility of the endorser contributed 63.1% of its influence on buying interest which means a strong influence and the remaining 36.9% was influenced by other factors outside the factors studied. This study concluded that there is an influence of endorsers on consumers' buying interest.